A pseudokinase version of the histidine kinase ChrS promotes high heme tolerance of Corynebacterium glutamicum - Krüger, Aileen; Frunzke, Julia (Frontiers in Microbiology, 2022)
Heme is an essential cofactor for almost all living cells by acting as prosthetic group for various proteins or serving as alternative iron source. However, elevated levels are highly toxic for cells. Several corynebacterial species employ two paralogous, heme-responsive two-component systems, ChrSA and HrrSA, to cope with heme stress and to maintain intracellular heme homeostasis. Significant cross-talk at the level of phosphorylation between these systems was previously demonstrated. In this study, we have performed a laboratory evolution experiment to adapt Corynebacterium glutamicum to increasing heme levels. Isolated strains showed a highly increased tolerance to heme growing at concentrations of up to 100 µM. The strain featuring the highest heme tolerance harbored a frameshift mutation in the catalytical and ATPase-domain (CA-domain) of the chrS gene encoding a heme-responsive histidine kinase gene, converting it into a catalytically-inactive pseudokinase (ChrS_CA-fs). Reintroduction of the respective mutation in the parental C. glutamicum strain confirmed high heme tolerance and showed a drastic upregulation of hrtBA encoding a heme export system, conserved in Firmicutes and Actinobacteria. The strain encoding the ChrS pseudokinase variant showed significantly higher heme tolerance than a strain lacking chrS. Mutational analysis revealed that induction of hrtBA in the evolved strain is solely mediated via the cross-phosphorylation of the response regulator ChrA by the kinase HrrS and BACTH assays revealed the formation of heterodimers between HrrS and ChrS. Overall, our results emphasize an important role of the ChrS pseudokinase in high heme tolerance of the evolved C. glutamicum and demonstrate the promiscuity in heme-dependent signaling of the paralogous two-component systems facilitating fast adaptation to changing environmental conditions.